N and P Nutrient Uptake Efficiency with Various Combinations of Organic and Biological Fertilization in Biosaline Rice Crops in Saline Soil - Sahlan, Nabilah Nur Fikriyyah; Susilowati, Lolita Endang; Dewi, Rika Andriati Sukma (Jurnal Keteknikan Pertanian Tropis dan Biosistem, 2026)
Salt-affected soils are marginal environments that constrain plant growth by reducing nitrogen (N) and phosphorus (P) availability and uptake efficiency. This study aimed to evaluate the effects of integrated fertilization combining inorganic, organic, and biofertilizers on N and P uptake and nutrient use efficiency in Biosalin rice grown under saline conditions. The experiment was conducted in West Lombok, Indonesia, using a randomized complete block design with nine treatments and three replications. Measured parameters included canopy dry weight, nutrient content, nutrient uptake, and recovery efficiency of N and P. The results showed that treatment M8 (50% inorganic fertilizer + cattle manure + phosphate-solubilizing bacteria + ACC-deaminase) produced the highest biomass and nutrient use efficiency. In contrast, treatment M4 resulted in the highest nutrient uptake but lower efficiency. These findings indicate that greater nutrient uptake does not necessarily translate into improved plant growth under saline conditions, and that nutrient use efficiency is a more critical determinant of plant performance. The integration of organic and biofertilizers significantly enhanced nutrient efficiency and enabled a 50% reduction in inorganic fertilizer application. Therefore, integrated fertilization represents a more efficient and sustainable strategy for rice cultivation in salt-affected soils.